how to factorise 9(2a-b)whole square -4(2a-b)-13

Asked by amikha s | 6th Sep, 2012, 11:34: AM

Expert Answer:

To factorise the polynomial, 9(2a - b)2 - 4(2a - b) -13, consider x = (2a - b)

 

So, 9(2a - b)2 - 4(2a - b) -13

= 9x2 - 4x -13

= 9x2 + 9x - 13x -13

= 9x(x + 1) - 13(x + 1) 

= (x + 1) (9x - 13)

= [(2a - b) + 1] [9(2a - b) - 13]                     [Since x = (2a - b)]

= (2a - b + 1) (18a - 9b - 13)

Answered by  | 6th Sep, 2012, 12:22: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.